Assessment of Pozzolanic Activity Using Methods Based on the Measurement of Electrical Conductivity of Suspensions of Portland Cement and Pozzolan - Sergio Velázquez (Materials, 2014)
The use of methods based on measuring electrical conductivity to assess pozzolanic activity has recently been used primarily in aqueous suspensions of pozzolan: calcium hydroxide. However, the use of similar methods in suspensions of cement with pozzolans has not been widely studied. This paper proposes a new method for rapid assessment of the pozzolanic activity of mineral admixtures in aqueous cement suspensions. In this study, the conditions for the application of the method were optimized, such as time, temperature, w/c ratio and dosage procedure. Finally, results are presented from the application of this method for characterizing the pozzolanic activity of the spent catalytic cracking catalyst. These results corroborate as previously reported, namely the high reactivity of this pozzolan obtained by other methods, such as thermogravimetry or evolution of the mechanical strength. In addition, the pozzolanic activity of the catalyst was compared with other pozzolans such as metakaolin and silica fume.